Doing (and undoing) privilege: evaluating how public policy drives health inequities - Ashley Schram; Amy Carrad; Belinda Townsend; Patrick Harris; Fran Baum; Lucie Rychetnik; Steven Allender; Melanie Pescud; Nicholas Frank; Megan Arthur; Sharon Friel (Critical Public Health)
In an era marked by persistent health inequities, this commentary moves beyond the conventional focus on disadvantage and individual-level interventions to present novel conceptual and analytical thinking that illuminates the role of structurally entrenched advantage. We present a multi-level conceptualisation of privilege through which the structural drivers of health inequities can be examined and the reciprocal relationship between privilege and public policy explored, shedding light on how these forces shape and reinforce one another. Building on that foundation, we propose an innovative research agenda that scrutinises the ideas, mechanisms, and outcomes of resource accumulation and distribution in public policy. We aim to lay the groundwork for developing and evaluating policy interventions through a new lens to address the root causes of inequities in health, paving the way for more equitable and healthy societies.